Carnosol and its analogues attenuate muscle atrophy and fat lipolysis induced by cancer cachexia. Issue 3 (5th May 2021) - Lu, Shanshan; Li, Yiwei; Shen, Qiang; Zhang, Wanli; Gu, Xiaofan; Ma, Mingliang; Li, Yiming; Zhang, Liuqiang; Liu, Xuan; Zhang, Xiongwen
Abstract: Background: Cancer cachexia is a multifactorial debilitating syndrome that directly accounts for more than 20% of cancer deaths while there is no effective therapeutic approach for treatment of cancer cachexia. Carnosol (CS) is a bioactive diterpene compound present in Lamiaceae spp., which has been demonstrated to have antioxidant, anti‐inflammatory, and anticancer properties. But its effects on cancer cachexia and the possible mechanism remain a mystery. Methods: The in vitro cell models of C2C12 myotube atrophy and 3T3‐L1 mature adipocyte lipolysis were used to check the activities of CS and its synthesized analogues. C26 tumour‐bearing BALB/c mice were applied as the animal model to examine their therapeutic effects on cancer cachexia in vivo . Levels of related signal proteins in both in vitro and in vivo experiments were examined using western blotting to study the possible mechanisms. Results: Carnosol and its analogues [dimethyl‐carnosol (DCS) and dimethyl‐carnosol‐D6 (DCSD)] alleviated myotube atrophy of C2C12 myotubes and lipolysis of 3T3‐L1 adipocytes in vitro . Interestingly, CS and its analogues exhibited stronger inhibitive effects on muscle atrophy induced by tumour necrosis factor‐α (TNF‐α) (CS, P < 0.001; DCS, P < 0.001; DCSD, P < 0.001) in C2C12 myoblasts than on muscle atrophy induced by IL‐6 (CS, P < 0.05; DCS, P = 0.08; DCSD, P < 0.05). In a C26 tumour‐bearing mice model, administration of CS or its analogue DCSD significantly prevented body weight loss without affecting tumour size. At the end of the experiment, the body weight of mice treated with CS and DCSD was significantly increased by 11.09% ( P < 0.01) and 11.38% ( P < 0.01) compared with that of the C26 model group. CS and DCSD also improved the weight loss of epididymal adipose tissue in C26 model mice by 176.6% ( P < 0.01) and 48.2% ( P < 0.05) increase, respectively. CS and DCSD treatment partly preserved gastrocnemius myofibres cross‐sectional area. CS treatment decreased the serum level of TNF‐α (−95.02%, P < 0.01) but not IL‐6 in C26 tumour‐bearing mice. Inhibition on NF‐κB and activation of Akt signalling pathway were involved in the ameliorating effects of CS and its analogues on muscle wasting both in vitro and in vivo . CS and its analogues also alleviated adipose tissue loss by inhibiting NF‐κB and AMPK signalling pathways both in vitro and in vivo . Conclusions: CS and its analogues exhibited anticachexia effects mainly by inhibiting TNF‐α/NF‐κB pathway and decreasing muscle and adipose tissue loss. CS and its analogues might be promising drug candidates for the treatment of cancer cachexia.